2018
DOI: 10.1177/1077800418788107
|View full text |Cite
|
Sign up to set email alerts
|

YouTube Generated Video Clips as Qualitative Research Data: One Researcher’s Reflections on the Process

Abstract: The ever-developing arena of social media blurs lines separating public and private spheres. Voluntary usage of social media platforms transforms users’ personal and sometimes private imaginings into publicly accessible artifacts. The entanglement of these two domains demands society’s consideration as policy makers, employers, and qualitative inquirers contend with making meaning of messages initiated within the social media sphere in a world extending beyond it. In this article, I reflect on interplay with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
(28 reference statements)
0
25
0
3
Order By: Relevance
“…This study used a qualitative research method with an incremental case study approach (Creswell, 2007;Hartley, 2004;Saldana, 2011;Simons, 2014;Yin, 2003). Data collection was carried out using unstructured interview technique (Saldana, 2011), direct observation (Walshe, Ewing, & Griffiths, 2011), documentation study (Yin, 2003) and the use of video recordings (Adami, 2009;Heath, Hindmarsh, & Luff, 2010;Jewitt, 2012;Patterson, 2018). This study used the Interactive Model Data Analysis and triangulation of data sources, methods, and data types for validating the data (Miles, Huberman, & Saldana, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This study used a qualitative research method with an incremental case study approach (Creswell, 2007;Hartley, 2004;Saldana, 2011;Simons, 2014;Yin, 2003). Data collection was carried out using unstructured interview technique (Saldana, 2011), direct observation (Walshe, Ewing, & Griffiths, 2011), documentation study (Yin, 2003) and the use of video recordings (Adami, 2009;Heath, Hindmarsh, & Luff, 2010;Jewitt, 2012;Patterson, 2018). This study used the Interactive Model Data Analysis and triangulation of data sources, methods, and data types for validating the data (Miles, Huberman, & Saldana, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…However, social media did provide students with avenues to share resources and ideas. The social media tools used include Skype (Xiangming, & Song, 2018), Youtube (Patterson, 2018), GoogleDocs (Aucoin, 2014), WhatsApp (Saw, Abbott, Donaghey, & McDonald, 2013), and Wikis (Abdelmalak (2015). Rohr and Costello (2015) also found that Twitter is a quick and efficient way students feel connected to their classmates and the course material.…”
Section: The Context Of the Studymentioning
confidence: 99%
“…A preliminary survey conducted earlier and gave feedback about digital media and marketing communication used based on marketing strategi of the firm. Some of the digital media were still relevant during the process of collecting data, thus the digital media used (or previously used) are Website [27], Email [28], Instagram [29], Facebook [30], Twitter [31], YouTube [32], WhatsApp [33], Line [34], and Blackberry Messenger [35]. And the marketing communication used are Advertising, Personal Selling, Publicity & Public Relation, and Customer Service [36].…”
Section: Introductionmentioning
confidence: 99%